BRAND AUDIT: A CASE STUDY OF BANGO - Subekti, Muhammad Raka Rio Imam; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2018)
Abstract.Bango is a soy sauce company originated in Indonesia. Bango was established in 1928. Bango through Unilever Internship Program website has mentioned that they are currently searching for ideas in order to penetrate the millennial generations. This issue is related with Keller’s brand equity measurement goals which is to manage brand overtime. The researcher focused on the brand audit which is the first step of brand equity measurement. A brand audit of Bango’s sweet soy sauce is required to identify the brand associations then have improvement recommendation for Bango. Brand Audit in this research uses brand inventory and brand exploratory. Based on the findings and the analysis from brand audit analysis through brand dynamics and X-SBM, the recommendation is to gain trustworthiness by creating a two way communication with fast response, and also an narrative advertisement showing how trustworthy is Unilever and Bango. Maximizing the usage of Social Media as Bango and utilize to the maximum efforts in order to reach the millennial, because based on the findings by Pew Research Center, millennial tend to use social media. Create an advertisement in YouTube with an easy to understand and meaningful advertisement Keywords: bango, brand audit,  brand exploratory, brand inventory, sweet soy sauce